Toward Developing Energy Star Rating Development in Jordan - Yakhlef, Majida; Ghadi, Yazeed Yasin; Baniyounes, Ali M.; Alnabulsi, Mazen; Radwan, Eyad (International Journal of Energy Economics and Policy, 2020)
The objective of this article is to provide an efficient means of enforcing green building in Jordan, the Middle East. The paper is proposing assessment tool of Energy Star Rating Scheme and also explaining its role for achieving sustainable development during buildings lifecycle and hence reducing energy and water usage. The Scheme development will remove considerable environmental, social and economic issues as Jordan is a country that renowned for its poor energy and water resources. The article provides technical aspects, means, technologies and processes for proposing and implementation Green star ratings for buildings. The star ratings are based on integrating renewable energy technologies, water recourses and its consumption management and waste recycling and its management throughout the buildings’ life cycle including its design, installation and operation. Keywords: Energy star ratings, Energy and water, Sustainable energy, Environment JEL Classifications: K32, O13 DOI: https://doi.org/10.32479/ijeep.7982